The preferred teaching methods among music education students / Sabinus Marcus - Marcus, Sabinus (2016)
The purpose of this study is to investigate the preferred teaching methods among music education students and to identify their reasons why they choose that method of teaching. In addition, this study also to know the teaching method that their lecturer used usually in class. Fifty undergraduate students taking Bachelor of Music Education in Faculty of Music UiTM were randomly selected about their preferred teaching method in learning subjects which need a lot of reading. Subjects which need a lot of reading here are ENT 530 Entrepreneurship, EDU 430 fundamental of counselling and EDU 550 education psychology. Most of the students rated discussion method as the best teaching method. Reasons may include, this method helps them to understand more on the topics and also helps them to increase their interpersonal skill. Furthermore, it gives them opportunity to sharing their ideas or points to the topics that they are discussing, thus learn to respect others point of view. Second most preferred teaching method will be demonstration method, for the reason that it helps them to understand more on the topic. As this method of teaching conducted in class, they can see clearly how the theory works and know how to apply it in the real world.